Epidemiological and clinical variability of amyotrophic lateral sclerosis between geographic areas and populations : focus on Africa and Latin America - (:unkn) unknown (My University, 2019)
Amyotrophic lateral sclerosis (ALS) is a rare neurodegenerative disorder with an invariable fatal outcome. Current evidence supports ALS variability in terms of incidence, mortality and clinical features between geographic areas and populations. This dissertation offers an updated review of ALS heterogeneity along with two original epidemiological and clinical studies in Africa and Latin America. First, a multicenter hospital-based study in eight African countries that described and compared the sociodemographic characteristics, clinical features, treatments, prognoses and survival times of patients with ALS. Certain specific characteristics were different in African cases compared to Western cases like higher proportion of male patients, younger age at onset, lower proportion of bulbar onset and shorter survival than expected. Subcontinental location and riluzole treatment are independently associated with survival. Second, a population-based study estimated ALS mortality rates in Ecuador, a predominant admixed population. The findings support a lower ALS occurrence in admixed populations from Latin America compared to European and Northern American populations. Standardized mortality rates were compared among ethnic groups with significant differences between admixed and other ethnic groups (Indigenous, Asians and Arabs). This work provides original and reliable data to improve our knowledge of ALS in Africa and Latin America. An international and multidisciplinary collaboration is crucial to understand ALS variability in different populations.
Keywords: African Research